2018
DOI: 10.18203/2349-2902.isj20184744
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of early exploration versus conservative approach for management of appendiceal mass

Abstract: Background: Acute appendicitis is the most common reason for emergency abdominal surgery. Acute appendicitis is ranging from mild inflammation of mucous membrane to gangrene, perforation and peritonitis. Appendicular mass is one of its early complication developing in 2 to 6 % cases of acute appendicitis within 48 hours of attack. Objective of this study was to evaluate the outcome of early surgical exploration and its complications in respect to conservative management followed by interval appendectomy for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…A Nigerian study found the incidence of 2.9% while for Bhandari et al it was 2% to 6%. The majority of cases were found to be in the age group of 21 to 30 years (35.71%) and the gender ratio of male:female was around 2:1, which is similar to other studies [21,23]. A study by Pandey et al revealed the majority of the patients (48.39%) from the age group of 21 to 30 years with male:female was approximately 2:1 [21].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A Nigerian study found the incidence of 2.9% while for Bhandari et al it was 2% to 6%. The majority of cases were found to be in the age group of 21 to 30 years (35.71%) and the gender ratio of male:female was around 2:1, which is similar to other studies [21,23]. A study by Pandey et al revealed the majority of the patients (48.39%) from the age group of 21 to 30 years with male:female was approximately 2:1 [21].…”
Section: Discussionsupporting
confidence: 86%
“…A study by Pandey et al revealed the majority of the patients (48.39%) from the age group of 21 to 30 years with male:female was approximately 2:1 [21]. Similarly, another study from Northern India showed 41.3% were from the age group of 21 to 30 years while male and female patients were 31 and 15 respectively [23]. A total of 44 patients (39.28%) had pain in the right iliac fossa for four days.…”
Section: Discussionmentioning
confidence: 94%